Community composition of zooplankton exported from a shallow polymictic reservoir linked to wind conditions - Nathan Ruhl; Desireé Haban; Caitlyn Czajkowski; Michael Grove; Courtney E. Richmond (PeerJ, 2019)
Zooplankton exported from lentic systems provision lotic systems with easily captured, consumed, and assimilated prey items. Previous studies have demonstrated that the community composition of zooplankton exports (CCZE) vary over time, which introduces temporal differences in lotic resource availability (zooplankton prey) in downstream habitats. In the study presented here, we monitored variation in CCZE from a polymictic reservoir outfall in response to physical–chemical and atmospheric conditions bi-hourly over three different 24-h periods. Community composition of zooplankton export varied over the course of the day, and exports were most closely associated with wind directionality. Future studies of temporal variation in CCZE should incorporate wind conditions, especially in shallow systems where holomixis occurs frequently. Polymictic reservoirs are becoming increasingly common as the global pace of small dam construction quickens, making both the identification of factors influencing CCZE and the impact of zooplankton exports on local biodiversity and ecosystem function increasingly important to understand.